2021
DOI: 10.1177/15412040211029991
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Arrest Risk Perception Formation in the Association Between Psychopathy and Aggressive Offending

Abstract: Research on the role of risk perception as a mechanism linking personality traits and behavioral outcomes is limited. The current study assessed a developmental model of the influence of psychopathic traits (PPTs) on the between- and within-individual variation in perceptions of risk and aggressive offending. Multivariate latent growth curve models were used to estimate the role of risk perceptions in the association between PPTs and aggressive offending in a sample of 1,354 adjudicated youths. The results ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 90 publications
1
3
0
Order By: Relevance
“…With respect to the multiple regression models, all models of risk context of the ERS, except for the risk-perception model in female adolescents, predicted engagement in risktaking behaviors, in line with previous research (e.g., MacPherson et al, 2010;Andrews et al, 2020Altikriti et al, 2021. More specifically, the context of expected benefits in the evolutionary domains was the model which explained the highest variance of risk-taking behaviors, both in female and male adolescents, as it has been found in previous research (Cauffman et al, 2010;Mantzouranis and Zimmermann, 2010).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…With respect to the multiple regression models, all models of risk context of the ERS, except for the risk-perception model in female adolescents, predicted engagement in risktaking behaviors, in line with previous research (e.g., MacPherson et al, 2010;Andrews et al, 2020Altikriti et al, 2021. More specifically, the context of expected benefits in the evolutionary domains was the model which explained the highest variance of risk-taking behaviors, both in female and male adolescents, as it has been found in previous research (Cauffman et al, 2010;Mantzouranis and Zimmermann, 2010).…”
Section: Discussionsupporting
confidence: 85%
“…In line with the risk-return framework, it has been demonstrated that adolescents consider both the risks and benefits of taking part in risk-taking behaviors ( Gibbons et al, 2009 ; Maslowsky et al, 2011 ). With respect to risk perception, it has been found that lower risk perception is positively related to binge drinking, sexual risk-taking, criminal behaviors, extreme sports and financial risks ( Kershaw et al, 2003 ; Reniers et al, 2016 ; Martínez-Montilla et al, 2020 ; Altikriti et al, 2021 ), though higher risk perception has also been found to relate positively to risk-taking behaviors like speeding and drink-driving ( Hatfield and Fernandes, 2009 ). Nevertheless, expected benefits in risk-taking behaviors is more strongly associated with the engagement in these behaviors than risk perception in adolescents ( Cauffman et al, 2010 ; Mantzouranis and Zimmermann, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pederson et al (2020) states that rewards (encouraging words; praises) and punishment (certain penalty) are interventions that positively impact male juveniles in terms of self-transformation and their behaviors. Altikriti, Nedelec, and Silver (2021) find that rewards and punishments help individuals choose appropriate behaviors and vice versa. Studies also found that with punishment, individuals won't repeat their wrongdoings.…”
Section: Rehabilitation Process and How To Achieve It?mentioning
confidence: 99%
“…Further, whereas Laub and Sampson (2003) suggested that adult roles influence identity changes, identity change in adult roles may be unlikely for persons with psychopathy traits given that such traits include an uncaring and unemphatic attachment style, cognitive inflexibility, and sense of entitlement, even in stable relationships with prosocial persons (Forth et al, 2022). Whereas Laub and Sampson (2003) suggested that new social roles increase time spent with capable guardians who deter criminal behavior, because psychopathy is negatively associated with perceptions of risk (Altikriti et al, 2021), persons with psychopathy traits may be less responsive to capable guardians. In sum, although empirically untested, a lack of responsivity to informal social control among persons with psychopathy traits would challenge Laub and Sampson's (2003) assertion that desistance occurs by default.…”
Section: Revisiting Laub and Sampson's Life-course Principles Through...mentioning
confidence: 99%